1969
DOI: 10.1111/j.1469-8137.1969.tb06416.x
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARISON OF SOME PROPERTIES OF VICILIN AND LEGUMIN ISOLATED FROM SEEDS OF PISUM SATIVUM, VICIA FABA AND CICER ARIETINUM

Abstract: SUMMARYA comparison has been made of the globulins, vicilin and legumin, prepared by isoelectric precipitation, of the seeds of three species of the Vicieae, namely Pisum sativum, Viciafaba and Cicer arietinum. Their amino acid composition, band patterns after electrophoresis upon polacrylamide-urea gels, fingerprint patterns of their tryptic digests and N-terminal amino acids were compared. Considerable portions of the amino acid sequences of vicilin and legumin of Pisum sativum are probably the same or very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0
1

Year Published

1971
1971
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 9 publications
(12 reference statements)
4
21
0
1
Order By: Relevance
“…Despite the considerable variation in subunit patterns exhibited by the legumin variants (see below) they all possessed only the three N-terminal groups (leucine, threonine and glycine) previously observed for Pisum sativum (Jackson et at., 1969) and Vicia faba (Wright and Boulter, 1974) legumin. In every case the relative intensities of dansyl-end-groups were leucine > glycine > threonine and in one case (JI 849) dansyl-threonine was barely discernible.…”
Section: Results (I) Variation In Leguminmentioning
confidence: 99%
“…Despite the considerable variation in subunit patterns exhibited by the legumin variants (see below) they all possessed only the three N-terminal groups (leucine, threonine and glycine) previously observed for Pisum sativum (Jackson et at., 1969) and Vicia faba (Wright and Boulter, 1974) legumin. In every case the relative intensities of dansyl-end-groups were leucine > glycine > threonine and in one case (JI 849) dansyl-threonine was barely discernible.…”
Section: Results (I) Variation In Leguminmentioning
confidence: 99%
“…O predomínio da fração globulina tem despertado crescente interesse pelo isolamento e caracterização dessa fração em diferentes gêneros e espécies, destacando-se Vicia faba [40], Pisum sativum [19], Glycine max [21] e Phaseolus [8,38], entre outros [13]. Característi-cas distintas de solubilidade em sal, coeficiente de sedimentação em ultracentrífuga e peso molecular tem revelado a presença de duas frações globulínicas majoritárias, onde na grande maioria dos gêneros parece predominar a fração 11S (tipo legumina), enquanto no Phaseolus a 7S (tipo vicilina) é a fração principal [13].…”
Section: -Introduçãounclassified
“…Gel filtration has been used (16) and also repeated isoelectric precipitation (2,16 It has been suggested that legumin and vicilin are closely related, have sequences of amino acids in common (16), and that immunologically they cross react reciprocally (19). There are two possible explanations for this cross-reactivity.…”
Section: Isolation and Characterisation Of Legumin And Vicilinmentioning
confidence: 99%
“…Varner and Schidlovsky (29) showed globulins to be localized in protein bodies within pea cotyledons. Jackson et al (16) analyzed legumin and vicilin from Vicia faba L. by fingerprinting tryptic digests and identifying the N-terminal amino acids. The subunits of legumin have been studied by Bailey and Boulter (2).…”
mentioning
confidence: 99%